MARITIME TRANSPORT AND TOURISM SUSTAINABLE DEVELOPMENT - Elson Thana (European Scientific Journal, ESJ, 2013)
Maritime transport worldwide had always been and still remains to be a very important catalyst for the economic development. It is the backbone of international trade and key engine driving globalization. Around 80% of global trade by volume and over 70% by value is carried by sea and is handled by ports worldwide; these shares are even higher in the case of most developing countries.547 In Adriatic and Ionian countries, maritime transport is playing an important role due to the geographical position, and has been a key factor for the development of trade and the maintenance of contacts between them and the rest of the world. Currently maritime transport has become an efficient way to attract various visiting tourists, and therefore, plays an important role in the development of tourism in Mediterranean. Recently, EU and many International and National Organizations are paying a special attention for the development and modernization of maritime transport, in order to play a more effective role in the framework of the sustainable development of transport, tourism and the economy in general. This paper will present an expanded view of the improvement of the legal framework and maritime infrastructure, aspects that directly affect the development of tourism. For this purpose, in this paper we will pose the progress of recent years in maritime transport and the legacy of the past with particular focus on its recent modernization.